2021
DOI: 10.1016/j.jad.2021.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Parental psychological distress and attitudes towards COVID-19 vaccination: A cross-sectional survey in Shenzhen, China

Abstract: Background Parental attitudes towards the vaccines play a key role in the success of the herd immunity for the COVID-19. Psychological health seemed to be a controversial determinant of vaccine hesitancy and remained to be investigated. This study attempted to measure parental psychological distress, attitudes towards the COVID-19 vaccine, and to explore the potential associations. Methods An online survey using convenience sampling method was conducted among parents wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 44 publications
3
58
8
Order By: Relevance
“…Our multivariate analysis revealed a positive relationship between parents’ self-perceived severity of COVID-19 and their intention to vaccinate their children. Several studies confirm our finding that risk perception of COVID-19 is a strong determinant of parents’ COVID-19 vaccine acceptance (Kelly et al, 2021; Skjefte et al, 2021; Xu et al, 2021; Yigit et al, 2021; Yilmaz and Sahin, 2021). In general, people who consider the COVID-19 as dangerous and life-threatening are those who are most willing to be vaccinated (Caserotti et al, 2021; Glöckner et al, 2020; Karlsson et al, 2021; Ward et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Our multivariate analysis revealed a positive relationship between parents’ self-perceived severity of COVID-19 and their intention to vaccinate their children. Several studies confirm our finding that risk perception of COVID-19 is a strong determinant of parents’ COVID-19 vaccine acceptance (Kelly et al, 2021; Skjefte et al, 2021; Xu et al, 2021; Yigit et al, 2021; Yilmaz and Sahin, 2021). In general, people who consider the COVID-19 as dangerous and life-threatening are those who are most willing to be vaccinated (Caserotti et al, 2021; Glöckner et al, 2020; Karlsson et al, 2021; Ward et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…According to our investigation, the proportion of COVID-19 vaccine hesitancy among reproductive women in China was 8.44%, which was lower than that in some provinces or territories of China (21)(22)(23)(24). For example, 87.5% would accept a vaccine with the most ideal attributes for their child, while with the least ideal attributes, these numbers dropped to 31.3% in Shanghai, China (22).…”
Section: Discussionmentioning
confidence: 62%
“…For example, 87.5% would accept a vaccine with the most ideal attributes for their child, while with the least ideal attributes, these numbers dropped to 31.3% in Shanghai, China (22). Xu et al reported that the proportion of COVID-19 vaccine hesitancy for their children was 27.3% in Shenzhen, China (23). Only 59.3% of parents reported willingness to avail COVID-19 vaccine for their children in Wuxi, China (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family member's support and feeling the child will take up vaccination were associated with higher parental acceptability [25]. Among almost 5000 parents within the school public health network of the same region, hesitancy was 27.3% and parents with psychological distress were more likely to be hesitant about vaccinating their children [26]. A self-administered online survey in Turkey at the same time as our phase 2 revealed much lower willingness to vaccinate children (36.3%) than in our survey, and in comparison to the rate of parents planning to get vaccinated themselves (59.9%).…”
Section: Discussionmentioning
confidence: 99%